2010
DOI: 10.1007/s12301-010-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary retention in women: Causes and management

Abstract: Objectives: Urinary retention in women is uncommon and there are numerous etiological factors. Most reported studies are from Europe and North America, with few studies from developing countries. The aim of this study was to review the etiology of urinary retention in women referred to our institution, a public sector hospital serving a largely indigent population. Patients and Methods: We reviewed the clinical records of all patients admitted with urinary retention to the Urology wards in our hospital during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A recent South African review, reporting on 31 women presenting with urinary retention over a 9-year period, identified urethral carcinoma (4/31) and cervical carcinoma (4/31) as the commonest underlying pathology [13]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent South African review, reporting on 31 women presenting with urinary retention over a 9-year period, identified urethral carcinoma (4/31) and cervical carcinoma (4/31) as the commonest underlying pathology [13]. …”
Section: Discussionmentioning
confidence: 99%